Modeling true intraindividual change: Studying correlates of variability in coping with low-control stress - Buško, Vesna; Kulenović, Alija (2005)
The paper presents an illustration of a particular class of structural equation models applied to the study of intraindividual variations in coping processes. Within this class of modeling procedures, true intraindividual change scores between two occasions of measurement correspond to the values of endogenous latent variables. Such a model specification further enables examining correlates and predictors of true intraindividual change between the measurements. Within the transactional stress and coping theory, the processes of coping are context-specific and varying across time and the attributes of concrete stressful situations. Nevertheless, substantial interindividual differences in the intraindividual change scores can still be found in the measures of coping with any kind of situational demands. The true change modeling procedures were hence employed to test the hypotheses on the antecedents and sources of interindividual differences in changes in the use of specific coping strategies. The data analyzed here were collected within follow-up study on the processes of coping and adjustment of recruits during military service (Buško, & Kulenović, 2003). Along with three broad situation-specific coping measures, personality data derived from NEOFFI questionnaire and the cognitive appraisals data, gathered on two occasions on the sample of 421 male participants were also used in this study. The tested structural equation models and the parameters obtained point to different patterns of relationships of latent state and latent change coping measures with particular personality and appraisal variables. The findings are discussed within the framework of transactional stress and coping theory and the context of low-control stressful situations.
Projekt MZOS
ENG